2018
DOI: 10.5797/jnet.tn.2017-0096
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Approach for Mechanical Thrombectomy of Posterior Circulation Stroke

Abstract: Objective: We report the mechanical thrombectomy (MT) of posterior circulation large vessel occlusion (pc-LVO) in which the transradial approach (TRA) was selected as an initial approach route to reduce the duration of treatment.Case Presentation: We performed MT using the TRA for four patients with pc-LVO between November 2015 and March 2017. The TRA was used as an initial approach route in patients in whom preoperative MRI showed that the right vertebral artery (VA) was predominant. In all patients, the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In MT with acute ischemic stroke in the posterior circulation, it has been reported that the transradial approach could be used as the primary access in patients where the approach from the right vertebral artery is viable, based on prior magnetic resonance (MR) angiography [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MT with acute ischemic stroke in the posterior circulation, it has been reported that the transradial approach could be used as the primary access in patients where the approach from the right vertebral artery is viable, based on prior magnetic resonance (MR) angiography [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MT with acute ischemic stroke in the posterior circulation, it has been reported that the transradial approach could be used as the primary access in patients where the approach from the right vertebral artery is viable, based on prior magnetic resonance (MR) angiography. 19 In order to select cases in which the transbrachial approach could be the first choice in the future, it is necessary for elderly patients to routinely undergo MR angiography or 3D-CT angiography that includes the aortic arch. In addition, the transbrachial approach is impossible for patients with stenotic lesions in the subclavian artery; MR angiography or 3D-CT angiography including the subclavian artery is therefore useful for detecting this before surgery.…”
Section: Described 15 Patients Who Underwentmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, various factors might cause difficulties in guiding catheter (GC) induction, including the aortic arch structure, arterial tortuosity or calcification, and atherosclerotic stenosis. [9][10][11][12][13][14][15][16][17][18][19][20] Previous studies have indicated that the interval between treatment initiation and final recanalization had positive correlation with GC induction and favorable prognosis. 3,[9][10][11][12][13][16][17][18][20][21][22][23] For better prognosis, prompt change in approach route is necessary when difficulties are encountered in GC induction through the right common femoral artery (CFA), the most easily accessible artery during MT.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Previous studies have indicated that the interval between treatment initiation and final recanalization had positive correlation with GC induction and favorable prognosis. 3,[9][10][11][12][13][16][17][18][20][21][22][23] For better prognosis, prompt change in approach route is necessary when difficulties are encountered in GC induction through the right common femoral artery (CFA), the most easily accessible artery during MT. 10,14,[16][17][18]20 Since MT is an emergency procedure, it is necessary to decrease door-to-puncture time and minimize pre-treatment examination period for improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation